Investigation by questionnaire for discomfort of painless temporomandibular sound - Abe, Masato; Mitsui, Maimi; Taniguchi, Wataru; Miyamura, Jyuichi; Yoda, Yasushi; Morita, Shin; Yoda, Tetsuya; Ono, Toaki; Sakamoto, Ichiro; Tsukahara, Hiroyasu; Enomoto, Shoji (Journal of the Japanese Society for the Temporomandibular Joint, 1997)
The purpose of this study was to examine how the patients feel about the discomfort of painless temporomandibular sound, which was investigated by questionnaire. The qestionnaire contains: emitted time, duration, and discomfort of temporomandibular sound, the reason for coming to hospital, etc. The cases comprised 28 males and 83 females and the average age was 29.8 years. As a result, 92.9 % patients felt discomfort of temporomandibular sound and 84.6 % of these patients expected some kind of treatment.